A Note on Obata Equations on Manifolds with Boundary (Journal of Mathematical Study, 2022)
We analyze complete manifolds with boundary which admit solutions to Obata type equations $ abla^2 f- fg=0$ and $ abla^2 f=g$ under various boundary conditions. Given the existence of interior critical points, such manifolds are domains in the hyperbolic space and the Euclidean space respectively.